Influence of Development of the Organization of the Operational Accounting and Control on the Enterprises' Management of Machine-Building in Ukraine - Olga Starenka (European Financial and Accounting Journal, 2015)
The article considers the operational management system of machine-building enterprises in Ukraine under the conditions of interpenetration of accounting and control functions and their deep integration due to shift of the control centres with the centres of operational decision-making. It has been proved that control timely influences behaviour and conditions of economic objects using target indicators, norms and regulations, estimates and the data of operational accounting, thus it takes active part in shaping the final results of running the enterprise. This explains its importance in the operational management system. It has been considered that the conditions of economic activity of industrial enterprises are changing intensively under the influence of internal and external factors, which determines the requirement to obtain operational information about the enterprise performance and the achieved results of each department. This is possible due to operational accounting, which must be systemic and cover all business processes, since it influences the functioning of the whole system as the information base for monitoring, and its results constitute the basis for timely decision-making in management. It is proved that well organized system of the accounting and control allows not only to detect in due time shortcomings of the industrial enterprise activity, but also to carry their expeditious elimination out and to prevent their manifestations in the future.
Keywords: M41; M42; 650; Management; Operational accounting; Operational control